Poly-γ-glutamic acid: Recent achievements, diverse applications and future perspectives. (January 2022) - Wang, Limin; Chen, Shengbao; Yu, Bo
Abstract: Background: Poly-γ-glutamic acid (γ-PGA) is a chiral biopolymer composed of either l -glutamic acid or d -glutamic acid or both monomers in different ratios and repeating frequency. It is biodegradable, water-soluble, environmentally friendly, and edible, and has versatile industrial applications. Depending on the microbial producers, the molecular weights and stereochemical compositions of γ-PGA differ substantially, and exhibit great application diversity. It is crucial to control the structural diversity to produce tailor-made γ-PGA. Scope and approach: This review presents advances in γ-PGA synthesis in microorganisms and metabolic engineering strategies used to improve γ-PGA diversity. The fascinating roles of structural diversity in various applications and future research directions in γ-PGA bio-production are also discussed in this review. Key findings and conclusions: Obtaining the γ-PGA with specific stereoisomer and molecular weight is an indispensable step in the expanded uses of γ-PGA. With the development of metabolic engineering and synthetic biology, the production of tailored γ-PGA in a single host is possible. Highlights: γ-PGA is a chiral biopolymer and has versatile industrial applications. Several Bacillus species produce γ-PGA outside the cells. Different γ-PGA properties have different industrial applications. Metabolic engineering and synthetic biology make it possible to produce γ-PGA with specific properties.